New Direction of National Law Reform Through Revision of The Criminal Code - Sukma, Dara Pustika; Kurniawan, Itok Dwi (Rechtsvinding, 2025)
The revision of the Criminal Code (KUHP) is a strategic step in realizing the reform of national law based on the values of Pancasila and the 1945 Constitution of the Republic of Indonesia. The old Criminal Code as a product of Dutch colonialism (Wetboek van Strafrecht) is considered irrelevant to social, cultural, economic, political, and technological developments in Indonesia, which is undergoing reform. Through the establishment of the new Criminal Code, the government seeks to present a criminal law system that is more humane, fair, and reflects the nation's identity. This reform is also a form of legal decolonization and national independence in building a national legal system with Indonesian personality. This study aims to analyze the urgency of revising the Criminal Code in the context of national law reform and assess its implications for the criminal law system in Indonesia. Using a normative juridical approach, this study emphasizes that the revision of the Criminal Code is not just a textual change, but a substantial transformation towards a criminal law that is in accordance with the values of social justice and universal humanity.